2008
DOI: 10.1097/mej.0b013e32823a3cc1
|View full text |Cite
|
Sign up to set email alerts
|

Stroke thrombolysis in the emergency department as an alternative service for community hospitals lacking a stroke unit

Abstract: According to the local infrastructural criteria and prerequisites described in this study, thrombolysis is a viable and feasible treatment option for stroke patients in emergency departments of French community hospitals. In the absence of an SU, this type of emergency treatment can be used as an alternative until SUs become more numerous throughout the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…In an ana lysis from the same registry that examined trends in use of tPA between 2003 and 2008, the adjusted odds ratio of thrombolysis was slightly higher in men compared with women (adjusted OR: 1.06; 95% CI: 1.00-1.12) [28]. In the USA, a study of consecutive ischemic stroke patients seen at 32 academic centers found that IV tPA treatments rates were comparable in men and women (7.5 vs 6.5%, respectively, p = 0.49) [29], while data from the Get With the Guidelines Stroke registry from 2003 to 2008 found that, among ischemic stroke cases who arrived within 2 h of symptom onset, Arrich (2008) [57] Barroso (2007) [58] Bray (2006) [59] Brown (2004) [60] Foerch (2007) [61] Heuschmann (2004) [62] Johnston (2001) [63] Kapral (2005) [64] Katzan (2000) [65] Qureshi (2005) [66] Reed (2001) [67] Reid (2008) [68] Schumacher (2007) [69] Schwammenthal (2004) [70] Walters (2005) [71] Weimar (2006) [72] Overall (95% CI)…”
Section: Utilization Of IV Tpamentioning
confidence: 99%
“…In an ana lysis from the same registry that examined trends in use of tPA between 2003 and 2008, the adjusted odds ratio of thrombolysis was slightly higher in men compared with women (adjusted OR: 1.06; 95% CI: 1.00-1.12) [28]. In the USA, a study of consecutive ischemic stroke patients seen at 32 academic centers found that IV tPA treatments rates were comparable in men and women (7.5 vs 6.5%, respectively, p = 0.49) [29], while data from the Get With the Guidelines Stroke registry from 2003 to 2008 found that, among ischemic stroke cases who arrived within 2 h of symptom onset, Arrich (2008) [57] Barroso (2007) [58] Bray (2006) [59] Brown (2004) [60] Foerch (2007) [61] Heuschmann (2004) [62] Johnston (2001) [63] Kapral (2005) [64] Katzan (2000) [65] Qureshi (2005) [66] Reed (2001) [67] Reid (2008) [68] Schumacher (2007) [69] Schwammenthal (2004) [70] Walters (2005) [71] Weimar (2006) [72] Overall (95% CI)…”
Section: Utilization Of IV Tpamentioning
confidence: 99%
“…Proper monitoring protocols for the use of intravenous tPA and other acute therapies should be developed and in place with adequate in-service training of key personnel. 35,83 Key ED personnel should participate in educational activities related to stroke diagnosis and treatment at least 2 times per year. 9 Written documents that detail the ED operations for managing patients with acute stroke should be provided.…”
Section: Emergency Departmentmentioning
confidence: 99%
“…This study reports on a novel training model in the setting of a regional strategy on the care of AIS, whose greatest challenges are the time-dependency of thrombolysis therapy and the accessibility of patients to this treatment [7,8]. The final test results demonstrated that trainees had acquired the relevant knowledge and skills.…”
Section: Discussionmentioning
confidence: 96%